Low-Back Pain Ratings for Lifetime, 1-Month Period, and Point Prevalences in a Large Occupational Population. (February 2014) - Thiese, Matthew S.; Hegmann, Kurt T.; Wood, Eric M.; Garg, Arun; Moore, J. Steven; Kapellusch, Jay M.; Foster, James; Greene, Tom; Stoddard, Greg; Biggs, Jeremy
Objective: This manuscript systematically quantifies multiple measures of low-back pain (LBP) prevalence by pain rating in a large, multisite cohort of workers. Background: Published LBP prevalence rates vary. Studies rely on one measure of LBP and none report prevalence stratified by pain rating. Method: Cross-sectional analyses of baseline data from a multicenter prospective cohort study were performed to evaluate differences in lifetime prevalence, 1-month period prevalence, and point prevalence of LBP. Workers were from 28 different employment settings in 4 diverse U.S. states. All workers completed computerized questionnaires and structured interviews. LBP prevalence measures were stratified by pain ratings. Results: A total of 828 subjects had complete health data at baseline. Lifetime prevalence, 1-month period prevalence, and point prevalence for any LBP (≥1/10) were 63.4%, 44.0%, and 20.8% respectively. Prevalence of LBP decreased with increasing pain ratings. As an example, using a threshold of LBP ≥ 3/10 pain, prevalence measures were 61.0%, 37.6%, and 16.7% respectively. A threshold of LBP ≥ 5/10 had prevalence measures of 51.2%, 22.9%, and 9.9% respectively. Age, systolic and diastolic blood pressure, high cholesterol, high blood pressure, and tobacco use were statistically significantly related to lifetime prevalence of LBP. Conclusion: Lifetime LBP prevalence, 1-month period prevalence, and point prevalence stratified by pain ratings demonstrate a wide variation of prevalence measures of LBP and self-reported pain ratings. Higher pain rating thresholds yield lower prevalence measures and may impact assessments of risk factors. Differences in pain ratings may allow for focused surveillance within an occupational cohort.